Lucas vs. Lucas : On Inequality and Growth - Cordoba, Juan Carlos (IMF Working Papers; Working Paper, 2007)
Lucas (2004) asserts that "Of the tendencies that are harmful to sound economics, the most seductive, and in my opinion the most poisonous, is to focus on questions of distribution... The potential for improving the lives of poor people by finding different ways of distributing current production is nothing compared to the apparently limitless potential of increasing production." In this paper we evaluate this claim using an extended version of Lucas' (1987) welfare-evaluation framework. Surprisingly, we find that the welfare costs of inequality outweigh the benefits of growth in most cases. These calculations support the case for a research agenda that treats not only growth but also inequality as a priority.